Prediction of Carang Mas Production Amount Using the Tsukamoto Fuzzy Inference System Method - Rendy Ahmadan Abdul Aziz, Maretha; Widaningrum, Ida; Karaman, Jamilah (Universitas Teknokrat Indonesia, 2024)
UD. ASTER is a company in the natural resource-based food processing business located in the renowned Sarangan tourism area in Magetan, East Java Province. Carang Mas is a type of processed cuisine made from sweet potato plants, commonly sold as a souvenir in Sarangan for tourists. Industry participants are encountering unpredictable demand. Currently, production planning and manufacturing of Carang Mas still rely on manual calculations, leading to overproduction and an accumulation of items. Carang Mas' endurance in this situation is limited to around one month. The company's sustainability is significantly impacted by demand unpredictability, necessitating the implementation of a predictive system for Carang Mas output every month. This prediction system utilizes the Fuzzy Tsukamoto approach because of its suitability for basic input and few computational requirements. The input variables are demand, stock, and manufacturing costs, with the output variable being production. The system's outcome is a forecast of Carang Mas output volumes achieved by the Fuzzy Tsukamoto technique. The algorithm's efficiency can be classified as O(1) in Big O notation, indicating constant time complexity. The MAPE test revealed a value of 4.0868 when comparing actual outcomes with expected results from January 2021 to December 2022.